2008
DOI: 10.1007/s12043-008-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Electron density distribution in Si and Ge using multipole, maximum entropy method and pair distribution function analysis

Abstract: The local, average and electronic structure of the semiconducting materials Si and Ge has been studied using multipole, maximum entropy method (MEM) and pair distribution function (PDF) analyses, using X-ray powder data. The covalent nature of bonding and the interaction between the atoms are clearly revealed by the two-dimensional MEM maps plotted on (1 0 0) and (1 1 0) planes and one-dimensional density along [1 0 0], [1 1 0] and [1 1 1] directions. The mid-bond electron densities between the atoms are 0.554… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…18 Therefore, the information on electron density distribution (EDD) is very useful in the characterization of the chemical bonds. However, the EDD data for Ge are currently limited to ambient pressure only [19][20][21][22] and no pressure dependence of EDD is available.…”
mentioning
confidence: 99%
“…18 Therefore, the information on electron density distribution (EDD) is very useful in the characterization of the chemical bonds. However, the EDD data for Ge are currently limited to ambient pressure only [19][20][21][22] and no pressure dependence of EDD is available.…”
mentioning
confidence: 99%
“…The MEM electron densities compiled from the experimental information are used for the visualization of the 3D electron density using the software VESTA (Koichi Momma and Fujio Izumi, Japan) [40]. The MEM electron density studies for various systems such as Na, V, Si, GaAs, Ge, etc., have already been reported elsewhere [41][42][43][44][45].…”
Section: Powder Xrd Data and Charge Densitymentioning
confidence: 76%
“…Several reports on the electron den sity studies of various materials have been reported such as semiconductors like GaAs [14] ZnTe [15], flu orides like CaF 2 [16], LiF, NaF [17], and intermetallic compound like MnHg [18] using MEM. PDF analysis of samples of elemental Si and Ge has been reported by Saravanan et al [9]. Other studies based on the PDF analysis were also reported [10,19,20].…”
Section: Charge Density Analysismentioning
confidence: 79%
“…In a work done by Saravanan et. al., [9] the mid bond density of silicon is found to be 0.554 e/Å 3 .…”
Section: Introductionmentioning
confidence: 94%